Wolfram|Alpha : computational knowledge engine.
Wolfram|Alpha introduces a fundamentally new way to get knowledge and answers— not by searching the web, but by doing dynamic computations based on a vast collection of built-in data, algorithms, and methods.
Keywords: Beelddatabank; Encyclopedieën